MODERN METHODS OF IMMOBILIZATION OF FRAGMENTS IN CHILDREN WITH MANDIBULAR FRACTURES (ANALYTICAL REVIEW) - Musaev , Sh.Sh.; Shomurodov, K.E. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
For the purpose of a comparative analysis of modern methods of immobilizing fragments of the lower jaw, data from sources of domestic and foreign literature are systematized. It has been established that the development and implementation of new, gentle methods for immobilizing the jaw is necessary for the treatment, rehabilitation and prevention of complications in children with mandibular fractures.